The Relationship Of State Law And Customary Law:: Reinforcement And Protection Of Customary Law In Constitutional Court Judgment - Asnawi Mubarok; Absori; Harun; Sheela Jayabalan (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Purpose of the study: This research analyzes the relationship between state law and customary law and Constitutional Court judgment in strengthening the rights of indigenous peoples and legal protection of the rights of indigenous peoples. Methodology: This article used normative legal research. Normative legal research is a scientific research procedure based on the logic of jurisprudence (doctrine) to seek truth from a normative perspective, which is conducted in the literature study in the form of relevant legal regulations and norms, especially in the Constitutional Court Judgment Number 35/PUU-X/2012, as well as other relevant sources. Results: This study reveals that recognition of the nature of the norms created by Indonesian indigenous peoples in the constitution is a facultative norm rather than imperative. Therefore, the state's obligation to recognize and respect indigenous peoples does not have strong binding force, so it is difficult to use apparent guidelines, procedures and mechanisms. This situation provokes conflicts, including between the government and society, society and entrepreneurs, and within society. The protection and reinforcement of indigenous communities still requires improvements and stronger law enforcement. Applications of this study: The research provides a comprehensive understanding analysis given that the interaction of state law with customary law or non-state laws both have influences and intersect with each other. However, conflicts between laws that apply to an area often let local laws to be defeated through the authorization process. The state has the right to issue and ratify all policies. State law should not eliminate the existence of customary law, but it is expected that shared likeliness can be sought so that it is consistent in its implementation. Novelty/ Originality of this study: This research gives a conceptual proposal of protecting indigenous peoples' land rights through: First, strengthening recognition. Indigenous communities whose customary land is in need for development should be recognized, not in the form of funds, but through the construction of public facilities or other forms of benefit to local communities. Second, establishing an independent institution under the President that resolves problems, conflicts, recognition, protection and promotion of the rights of indigenous peoples. Third, regulatory integration between ministries. Fourth, reinforcing the role of regional government and Regional Legislative Council. This conceptual proposal emphasizes the significance of respecting and protecting the rights of indigenous peoples before law, political recognition, autonomy and policies to ensure that the rights of indigenous peoples are respected and upheld. Keywords: Indigenous People, Legal Protection, Constitutional Court ABSTRAK Tujuan: Penelitian ini menganalisis tentang relasi hukum negara dengan hukum adat dan Putusan MK dalam penguatan hak masyarakat adat serta perlindungan hukum terhadap hak masyarakat adat Metodologi: Artikel ini menggunakan penelitian hukum normatif. Penelitian hukum normatif adalah suatu prosedur penelitian ilmiah berdasarkan logika yurisprudensi (doktrin) untuk mencari kebenaran dari sisi normatif, yang dilakukan dalam kajian bahan pustaka berupa peraturan dan norma hukum yang terkait terutama dalam putusan Mahkamah Konstitusi nomor 35/ PUU-X/2012, juga sumber lain yang terkait. Temuan: Kajian ini mengungkapkan bahwa pengakuan terhadap hakikat norma-norma yang diciptakan oleh masyarakat adat Indonesia dalam konstitusi adalah sebuah norma opsional dan bukan norma wajib. Oleh karena itu, kewajiban negara untuk mengakui dan menghormati masyarakat adat tidak mempunyai kekuatan mengikat yang kuat, sehingga tidak mudah untuk dijadikan pedoman, prosedur dan mekanisme yang lebih konkrit. Keadaan ini memunculkan banyak konflik, antara lain antara pemerintah dengan masyarakat, masyarakat dengan pengusaha, serta masyarakat dengan masyarakat. Perlindungan dan pemberdayaan masyarakat adat masih memerlukan perbaikan dan penegakan hukum yang lebih kuat. Kegunaan: Penelitian memberikan analisis pemahaman yang lebih komprehensif melihat bahwa interaksi hukum negara dengan hukum adat atau hukum yang bukan berasal dari negara sama-sama memiliki pengaruh dan saling bersinggungan, meskipun demikian konflik antar hukum yang berlaku atas suatu wilayah sering kali menyebabkan hukum lokal dikalahkan melalui proses otorisasi negara yang berhak mengeluarkan dan mengesahkan segala kebijakan. Hukum negara hendaknya tidak menyingkirkan keberadaan hukum adat, namun diharapkan dapat dicari titik-titik persamaan yang ada sehingga sejalan dalam pelaksanaannya. Kebaruan/Orisinalitas: Penelitian ini memberikan tawaran konsepsional perlindungan hak atas tanah masyarakat adat dapat melalui: Pertama, memperkuat recognitie. masyarakat adat yang tanah ulayatnya diperlukan untuk pembangunan harus diberikan pengakuan, bukan dalam bentuk uang, tetapi melalui pembangunan fasilitas umum atau bentuk lain yang bermanfaat bagi masyarakat setempat. Kedua, Membentuk lembaga independen di bawah Presiden yang menangani permasalahan, konflik, pengakuan, perlindungan dan pemajuan hak-hak masyarakat adat. Ketiga, Integrasi Regulasi antar Kementerian. Keempat, Penguatan Peran Pemerintah Daerah dan DPRD. Seluruh tawaran konsepsionel ini menekankan pentingnya menghormati dan melindungi hak-hak masyarakat adat dalam konteks hukum, pengakuan politik, otonomi, dan kebijakan untuk memastikan hak-hak masyarakat adat dihormati dan ditegakkan. Kata Kunci: Masyarakat Adat, Perlindungan Hukum, Mahkamah Konstitusi